A Visual Sensor for Domestic Service Robots - Muhammad Attamimi; Takayuki Nagai (JAREE (Journal on Advanced Research in Electrical Engineering), 2018)
In this study, we present a visual sensor for domestic service robots, which can capture both color information and three-dimensional information in real time, by calibrating a time of flight camera and two CCD cameras. The problem of occlusions is solved by the proposed occlusion detection algorithm. Since the proposed sensor uses two CCD cameras, missing color information of occluded pixels is compensated by one another. We conduct several evaluations to validate the proposed sensor, including investigation on object recognition task under occluded scenes using the visual sensor. The results revealed the effectiveness of proposed visual sensor. Keywords: Time of flight camera, visual sensor, camera calibration, occlusion detection, object recognition.